Perencanaan Dan Analisis Pembangkit Listrik Hybrid PLTS 4x50 Wp dan PLTB Tipe Darrieus Kapasitas 100 Watt - Mohamad Arya Iga Wardana; Mohammad Noor Hidayat; Rhezal Agung Ananto (UPT - P2M POLINEMA, 2022)
In this era energy resources are the main issues that are developing today, this is due to energy needs, offset by population growth and economic growth in Indonesia which is increasing, wind energy and solar energy are renewable energy sources that come from the process of natural that the possibility of the energy will never run out. Both of these energies can be used to produce electrical energy through a power generation process, namely the Hybrid Power Plant (PLTH). Hybrid power generation system is a combination of 2 or more alternative energy power plants, namely wind energy and solar heat. Previously installed 2x50 wp PLTS and Darieus type PLTB with a capacity of 100 watts due to the lack of supply for the 45 ah battery, 2x50 wp PLTS will be added so that charging the battery is faster and optimal and can be used as a reference to compare 2x100 Wp PLTS and 4x50 wp PLTS. The parameters used for this research are the state of the energy source and the electrical load in the futsal field of the State Polythecnic of Malang. in PLTS having an average solar radiation of about 882.14W/m2 can produce a power of 1,252.63 W using PV Monocrystaline of 1.42 m2